Teaching the Discipline of History in an Age of Standards (Springer Singapore, 2018)
This book discusses the discipline standards of History in Australian universities in order to help historians understand the Threshold Learning Outcomes and to assist in their practical application. It is divided into two sections: The first offers a scholarly exploration of contemporary issues in history teaching, while the second section discusses each of the Threshold Learning Outcomes and provides real-world examples of quality pedagogical practice. Although the book focuses on the discipline of history in Australia, other subjects and other countries are facing the same dilemmas. As such, it includes chapters that address the international context and bring an international perspective to the engagement with discipline standards. The innovation and leadership of this scholarly community represents a new stage in the transformation and renewal of history teaching.